Mutation in CDC42 Gene Set as a Response Biomarker for Immune Checkpoint Inhibitor Therapy - Kun Wang; Yingying Zhang; Zhaoming Su; Bei Wang; Yuanyang Zhou; Xiaochu Tong; Chengying Xie; Xiaomin Luo; Sulin Zhang; Mingyue Zheng (Cancer Medicine)
ABSTRACT Background Immune checkpoint inhibitors (ICIs) have achieved great success; however, a subset of patients exhibits no response. Consequently, there is a critical need for reliable predictive biomarkers. Our focus is on CDC42, which stimulates multiple signaling pathways promoting tumor growth. We hypothesize that an impaired function of CDC42 may serve as an indicator of a patient's response to ICI therapy. Methods We consider CDC42 and its downstream binding and effector proteins as a gene set, as mutations in these components could lead to defective CDC42 function. To elucidate the biomarker function of mutations within the CDC42 gene set, we curated a comprehensive discovery dataset that included seven ICI treatment cohorts. And we curated two ICI treatment cohorts for validation. We explored the mechanism based on The Cancer Genome Atlas database. We also examined whether combining a CDC42 inhibitor with ICI could enhance ICI's efficacy. Results Mutations in the CDC42 gene set were associated with improved overall survival and progression‐free survival. Furthermore, our analysis of immune response landscapes among different statuses of the CDC42 gene set supports its role as a biomarker. Animal experiments also revealed that the combination of the CDC42 inhibitor (ML141) with anti‐PD‐1 blockade can additively reduce tumor growth. Conclusions Our study suggests that the CDC42 gene set mutations could potentially serve as a novel biomarker for the clinical response to ICI treatment. This finding also provides insights into the potential of combining ICI and CDC42 inhibitor use for more efficient patient treatment.